2010
DOI: 10.1590/s1807-59322010000600012
|View full text |Cite
|
Sign up to set email alerts
|

Possible Links between Intestinal Permeablity and Food Processing: A Potential Therapeutic Niche for Glutamine

Abstract: Increased intestinal permeability is a likely cause of various pathologies, such as allergies and metabolic or even cardiovascular disturbances. Intestinal permeability is found in many severe clinical situations and in common disorders such as irritable bowel syndrome. In these conditions, substances that are normally unable to cross the epithelial barrier gain access to the systemic circulation. To illustrate the potential harmfulness of leaky gut, we present an argument based on examples linked to protein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 138 publications
(149 reference statements)
0
31
0
3
Order By: Relevance
“…Because it is almost impossible to achieve the same formulation used by drug manufacturers within the timeframe of the short half-lives of PET radionuclides, these types of studies are extremely difficult to perform. Rapin et al [47] suggested that normally dietary AGEs cross the intestinal wall poorly. However the elimination of AGEs might be very different if intestinal permeability (IP) is elevated by food allergies [48], and AGEs can affect the IP itself [49].…”
Section: Discussionmentioning
confidence: 99%
“…Because it is almost impossible to achieve the same formulation used by drug manufacturers within the timeframe of the short half-lives of PET radionuclides, these types of studies are extremely difficult to perform. Rapin et al [47] suggested that normally dietary AGEs cross the intestinal wall poorly. However the elimination of AGEs might be very different if intestinal permeability (IP) is elevated by food allergies [48], and AGEs can affect the IP itself [49].…”
Section: Discussionmentioning
confidence: 99%
“…It is the only HATi in clinical trials (Table 8) and exhibits great promise as a therapeutic agent. Its applications include atopic asthma (Kobayashi et al., 1997), chronic obstructive pulmonary disease (Rennolds et al., 2012), multiple myeloma (Ghoneum and Gollapudi, 2011), irritable bowel syndrome (Binion et al., 2008; Rapin and Wiernsperger, 2010), ulcerative colitis (Baliga et al., 2012), Crohn's disease (Mouzaoui et al., 2012), breast cancer (Nagaraju et al., 2012), Alzheimer's disease (Darvesh et al., 2012; Huang et al., 2012), pancreatic cancer (Dandawate et al., 2012; Veeraraghavan et al., 2011), colorectal cancer (Guo et al., 2012; Lin et al., 2011), diabetes (Abdel Aziz et al., 2012), and psoriasis (Kurd et al., 2008).…”
Section: Histone Modificators In Clinical Trialsmentioning
confidence: 99%
“…Increasing evidence supports distinct biological roles for each of the mammalian HDACs and it is probable that inhibition of specific members of the HDAC family will have specific functional consequences such as on gene expression, cell cycle regulation, proliferation, differentiation and apoptosis. A number of HDAC isoform-selective or -specific inhibitors are currently in development (Butler and Kozikowski, 2008;Estiu et al, 2008;Haggarty et al, 2003;Jones et al, 2008;Khan et al, 2008;Kozikowski et al, 2007;Moradei et al, 2008;Rasheed et al, 2007;Somoza et al, 2004). One question in the field of HDACi development, which remains unanswered, is whether selective inhibition of HDACs would be advantageous over broader-acting HDACi as anti-cancer agents.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…The effect of high temperatures on aminopeptides and lipids during processing in the presence of reducing sugars can lead to the formation of advanced glycation end products (AGEs). While these milk fractions may have been placed in the food system to potentially decrease intestinal permeability, the formation of AGEs can actually have the opposite effect (Rapin & Wiernsperger, 2010). Therefore it is of vital importance that the properties of the bioactive ingredients are considered, along with the composition of the food matrix and changes that occur to the product during processing and storage.…”
Section: Delivery Of Food Components To Infantsmentioning
confidence: 99%